Tìm mô đun của số phức z biết \(\left( {2z - 1} \right)\left( {1 + i} \right) + \left( {\overline z + 1} \right)\left( {1 - i} \right) = 2 - 2i\) .

Câu hỏi :

Tìm mô đun của số phức z biết \(\left( {2z - 1} \right)\left( {1 + i} \right) + \left( {\overline z  + 1} \right)\left( {1 - i} \right) = 2 - 2i\) .

A. \(\dfrac{1}{9}\)

B. \(\dfrac{{\sqrt 2 }}{3}\)

C. \(\dfrac{2}{9}\)

D. \(\dfrac{1}{3}\)

* Đáp án

B

* Hướng dẫn giải

Đặt \(z = a + bi \Rightarrow \overline z  = a - bi\)

Theo bài ra ta có:

\(\begin{array}{l}\,\,\,\,\,\,\left( {2z - 1} \right)\left( {1 + i} \right) + \left( {\overline z  + 1} \right)\left( {1 - i} \right) = 2 - 2i\\ \Leftrightarrow \left( {2a + 2bi - 1} \right)\left( {1 + i} \right) + \left( {a - bi + 1} \right)\left( {1 - i} \right) = 2 - 2i\\ \Leftrightarrow 2a + 2bi - 1 + 2ai - 2b - i + a - bi + 1 - ai - b - i = 2 - 2i\\ \Leftrightarrow \left( {3a - 3b} \right) + \left( {a + b - 2} \right)i = 2 - 2i\\ \Leftrightarrow \left\{ \begin{array}{l}3a - 3b = 2\\a + b - 2 =  - 2\end{array} \right. \Leftrightarrow \left\{ \begin{array}{l}a = \dfrac{1}{3}\\b = \dfrac{{ - 1}}{3}\end{array} \right. \Rightarrow z = \dfrac{1}{3} - \dfrac{1}{3}i \Rightarrow \left| z \right| = \sqrt {\dfrac{1}{9} + \dfrac{1}{9}}  = \dfrac{{\sqrt 2 }}{3}\end{array}\)

Chọn B.

Copyright © 2021 HOCTAP247